Ethics of Reconciliation – European Perspectives : Report on the 59th Annual Conference of the Societas Ethica (24.–27. August 2023) - Delere, Sarah (2024)
Sarah Delere berichtet von der 59. Jahrestagung der Societas Ethica, die vom 24.-27. August 2023 zum Thema Ethics of Reconciliation - European Perspectives in Sarajevo stattgefunden hat.
Keywords: Konferenzschrift